2018
DOI: 10.4314/tjpr.v17i8.20
|View full text |Cite
|
Sign up to set email alerts
|

New N-allylthiourea derivatives: Synthesis, molecular docking and <i>in vitro</i> cytotoxicity studies

Abstract: Purpose: To synthesise derivatives of N-allylthiourea and evaluate their anticancer activities against epidermal growth factor receptor (EGFR) using in silico and in vitro methods. Methods: Four compounds were synthesized using the Schotten-Baumann reaction. The structures of the synthesized compounds were confirmed using infrared (IR), proton nuclear magnetic resonance (1 H-NMR), carbon nuclear magnetic resonence (13 C-NMR) and electrospray ionization mass spectrometry (ESI-MS) methods. Molecular modeling was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 7 publications
(11 reference statements)
1
8
0
Order By: Relevance
“…The uptake was read by ELISA reader at a wavelength of 570 nm and the absorbance results read were converted into the percentage of life. [ 14 20 ]…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The uptake was read by ELISA reader at a wavelength of 570 nm and the absorbance results read were converted into the percentage of life. [ 14 20 ]…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, recent studies on allylthiourea derivatives showed the activity of these compounds against T47D and MCF-7 line breast cancer cells. [ 13 14 ] In this study, the activity of allylthiourea derivatives, namely N -benzoyl-3-allylthiourea (BATU) [ Figure 1 ], will be tested for the anticancer activity using MCF-7 cells with HER2 overexpression.…”
Section: Introductionmentioning
confidence: 99%
“…This was to ensure that the predictions of the data were available when it was being developed as an anticancer drug candidate. Changes in ADMET Predictor's predictions after the new phenylurea derivative had been synthesized would certainly occur and they would be different from those for the mother compounds [13].…”
Section: Figurementioning
confidence: 99%
“…The next step was to verify the binding of the active compound with several amino acids associated with the hydrogen bonds and the steric interactions. The final stage was involved docking the compound using Molegro Virtual Docker, version 5.5 until the rerank scores (RS) were obtained [11,13,14].…”
Section: Molecular Dockingmentioning
confidence: 99%
See 1 more Smart Citation